Lost Islamic History : Reclaiming Muslim Civilisation from the Past - Firas Alkhateeb (Lahore, Pakistan ILQA Publication, 2014)
A lively and eye-opening popular history of Islamic civilisation, this book seeks to redress the omission from the history books of many of the contributions of Muslim thinkers, scientists and theologians, not to mention rulers, statesmen and soldiers. It also includes portraits of key personalities, inventions and little-known historical nuggets.
Include Bibliography
Keywords: Islamic civilization -- Islamic countries -- Civilization